Trade and development report : report by the Secretariat of the United Nations Conference on Trade and Development. - United Nations Conference on Trade and Development (New York : United Nations, 1981)
This booklet is an overview of the programme and policy of the united nation conference on trade and development which was presented in 1988 under the trade and development report (UNCTAD/TDR/8
asm; 26/04/19
Loans
Keywords: Commerce; Economic development; Commerce; Commerce international; Commerce; Commerce; Economic development; Economic history; Welt; Developing countries